Modeling of Flywheel Hybrid Powertrain to Optimize Energy Consumption in Mechanical Hybrid Motorcycle - Abdul Manaf, Muhammad Zaidan; Nik Mohamed, Nik Abdullah; Zakaria, Mohamad Shukri; Saadun, Mohd Noor Asril; Mohd Hanafi, Mohd Hafidzal (Trans Tech Publications Ltd, 2013)
The creation of internal combustion engine is a significant milestone in power engineering world which simplified high mechanical energy demand jobs like moving vehicle and machinery. Even though the internal combustion engine gives lot of advantages, however, this type of engine is incapable to convert the heat energy from fuel combustion to the mechanical energy efficiently. Small capacity engine e.g. motorcycle engine having the power conversion efficiency between 25-30%. Therefore, alternative power source is required to support the internal combustion engine in order to increase the overall system efficiency. These phenomena give encouragement to implement the hybridization process. This is to increase the system efficiency in transferring power to the wheel. Hybridization processes e.g. flywheel as secondary power source can increase power transfer efficiency between 30%-80%. Hence, the purpose of this research is to develop the mathematical model of the power transfer efficiency of flywheel hybrid motorcycle by using back trace simulation method. This model will record the amount of energy use in acceleration phase of the driving cycle. Subsequently, the efficiency ratio of motorcycle power transfer is calculated and comparison of those ratios between the conventional motorcycle and the hybrid motorcycle is made. The outstanding results show that the hybrid motorcycle is capable to conserve the energy used up to 36% compare to the conventional motorcycle that wasted energy up to 200%. As a conclusion, flywheel as the secondary power source is capable to supply enough energy to propel the motorcycle forward.